Anti-N-Methyl-d-Aspartate (Anti-NMDA) Receptor Encephalitis Rapid and Sustained Clinical Improvement With Steroid Therapy Starting in the Late Phase - TÜRKDOĞAN, DİLŞAD; EKİNCİ, GAZANFER; ZAİMOĞLU, SENNUR (SAGE PUBLICATIONS INC, 2014)
Anti-N-methyl-d-aspartate (anti-NMDA) receptor encephalitis is an autoimmune/paraneoplastic encephalitis, with neurologic and psychiatric symptoms. Early and aggressive therapy has been shown to improve prognosis although problems with executive functions and memory have continued for several years. A 15-year-old girl had a history of initial symptoms including behavioral difficulties, poor attention, and frequent seizures progressing to a catatonia-like state, 2.5 months after onset of initial symptoms. Anti-NMDA receptor antibodies were detected in serum and cerebrospinal fluid. Subsequent to treatment with methylprednisolone starting 3 months after onset, motor skills, responsiveness, self-care, and speech improved rapidly. Her neuropsychologica profile assessed after 2 months showed global difficulties predominantly in attention, executive functions, memory, and visual perception, which moderately recovered in the 7th and 24th months, respectively. Contrary to current literature supporting the positive impact of early immunomodulatory therapy, a dramatic resolution of major neurologic and psychiatric symptoms was detected with steroid treatment given in the late phase.
Keywords: cortical atrophy; steroid treatment; autoimmune encephalitis; BRAIN ATROPHY; CHILDREN; EXPERIENCE